The humor after of the humor: concepts around Pablo Holberg´s Eden - Pablo Turnes (Antíteses, 2012)
At the beginning of 21st century comics production in Argentina have experienced the emergence of new methods of publication, promotion and circulation consisting of a series of devices whose complex relationship has redefined the authorial figureas well as a new reading audience. The passage from the Internet and digital formats to the book has established itself as post-industrial strategy in the context of the reconstitution of a diverse comics field, where the national tradition of humor serves as example of the mentioned changes